Epidemiology and Diagnostics of Cacao Swollen Shoot Disease in Ghana: Past Research Achievements and Knowledge Gaps to Guide Future Research - George A. Ameyaw; Owusu Domfeh; Ebenezer Gyamera (Viruses, 2023)
Cacao swollen shoot disease (CSSD) caused by complexes of cacao swollen shoot badnaviruses (family Caulimoviridae, genus Badnavirus) remains highly prevalent and devastating in West Africa. The disease continues to impact substantially on cacao yield loss, cacao tree mortality, and decline in foreign exchange income from cacao bean sales. Currently, the disease is estimated to have a prevalence rate of over 30% in Ghana, as assessed in the ongoing third country-wide surveillance program. Although achievements from past research interventions have greatly elucidated the etiology, biology, epidemiology, diagnostics, and management of the disease, there are some outstanding knowledge gaps. The role of these information gaps and their effect on CSSD epidemiology and prevalence remain unanswered. This paper summarizes existing scientific knowledge from past research achievements that have provided elucidation on CSSD epidemiology, management options, and guided future research. The discussion highlights the need for multidisciplinary research with modern tools and institutional collaborators to holistically bring clarity on knowledge gaps on pathogen biology, virus–host-–vector interactions, role of environmental and soil nutrient effects on CSSD severity, evolution pattern, role of alternative hosts on virus species diversity, vector population dynamics, and their overall impact on CSSD prevalence and integrated management in cacao plantations.